Screening and Brief Intervention for the use of alcohol and other drugs - Ângela Maria Mendes Abreu; Rafael Tavares Jomar; Gunnar Glauco de Cunto Taets; Maria Helena do Nascimento Souza; Daiane Belisário Fernandes (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to identify the lifetime use of alcohol and other drugs among users of the Family Health Strategy and apply Brief Intervention to problems related to the use of these substances. Method: a descriptive cross-sectional study where 1,031 users of the Family Health Strategy of the city of Rio de Janeiro answered a form with socio-demographic information and the Alcohol, Smoking and Substance Involvement Screening Test. Statistical analysis with simple frequency distribution was performed. Results: the most commonly used drugs in lifetime were alcohol and tobacco; among the illegal drugs, marijuana, hypnotics and cocaine/crack stood out. Those who received most Brief Intervention were users of tobacco, hypnotics, marijuana, cocaine/crack and alcohol. Conclusion: it is important to detect early problems associated with the use of alcohol and other drugs in Primary Care, since it has the promotion/protection of health and the prevention of diseases as priority health practices.